Limited plantar incision for flexor digitorum longus tendon harvest in surgical treatment of tibialis posterior tendon insufficiency. Issue 1 (January 2021) - Robberecht, Joris; Oddy, Michael J.
Highlights: The FDL tendon can be harvested through a limited plantar incision for use in flat foot surgery. The technique is reproducible, avoids the plantar nerves and maximises tendon length available. FDL/FHL interconnections do not require formal surgical release. Abstract: Background: Surgical correction of stage II tibialis posterior tendon dysfunction (TPTD) commonly utilises the Flexor Digitorum Longus (FDL) tendon to augment the tibialis posterior tendon. The aim of this study is to present our experience and clinical outcomes harvesting the FDL via a limited plantar incision technique. Methods: 25 flat foot operations for stage II TPTD were performed harvesting the FDL via a limited plantar incision centred half-way between the base of the heel to the base of the 2nd toe and two-thirds from the lateral border of the foot. Results: The FDL was isolated with no inter-tendonous connections requiring surgical division. There were no recorded cases of plantar nerve injury nor any technique-related complications observed. Conclusions: The plantar harvest technique for FDL is safe, provides a long tendon graft for transfer and limits the need for an extensive medial midfoot dissection.